Policy making and Southern distinctiveness - Morris, John C.; Mayer, Martin K.; Kenter, Robert C.; Anderson, R. Bruce (Routledge, Taylor & Francis Group, 2022)
"Policy Making and Southern Distinctiveness examines the uniqueness of Southern politics and their policy choices. While decades of scholarship on the politics of the American South have focused on partisanship and electoral outcomes as the primary elements of interest in Southern politics, few works have focused on the more practical outcomes of these political processes; specifically, comparing state policy choices of Southern states to non-Southern states. This book examines six different policy arenas, voting access, gun control, health care, reproductive rights, water and COVID-19 pandemic response, comparing policy choices in states in the South with states in the non-South. The authors find that the South is distinct in several, but not all, of the policy arenas examined. They conclude that the South as a region is unique because of exceptional degree of one-party control evident in the South, coupled with a long-standing preoccupation with partisanship and race-based politics. Policy Making and Southern Distinctiveness provides valuable insights into how and why states behave in the manner they do and where Southern states may diverge from the rest of the country. It will be of interest to scholars of Southern politics, state comparative policy, public policy, American politics, and federalism/intergovernmental relations"--
"Routledge Focus"--from cover
Keywords: Politische Kultur; Politische Beteiligung; USA -- Südstaaten; Political planning / Southern States; Political culture / Southern States; Dominant-party systems / Southern States; Southern States / Politics and government / 1951-; Dominant-party systems; Political culture; Political planning; Politics and government; Southern States; Since 1951